2017
DOI: 10.1002/bit.26378
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining opportunities for therapeutic protein production in eukaryotic microorganisms

Abstract: Antibodies are an important class of therapeutics and are predominantly produced in Chinese Hamster Ovary (CHO) cell lines. While this manufacturing platform is sufficiently productive to supply patient populations of currently approved therapies, it is unclear whether or not the current CHO platform can address two significant areas of need: affordable access to biologics for patients around the globe and production of unprecedented quantities needed for very large populations of patients. Novel approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 128 publications
(187 reference statements)
1
26
0
Order By: Relevance
“…Currently, almost all marketed antibodies are produced in mammalian cell cultures, and are therefore expensive and limited in availability [41]. Although the chloroplast does not possess the machinery for the glycosylation of proteins, work by the Mayfield's group has shown that the algal chloroplast is capable of correctly folding and assembling aglycosylated antibodies that are able to bind their target.…”
Section: Antibodies and Immunotoxinsmentioning
confidence: 99%
“…Currently, almost all marketed antibodies are produced in mammalian cell cultures, and are therefore expensive and limited in availability [41]. Although the chloroplast does not possess the machinery for the glycosylation of proteins, work by the Mayfield's group has shown that the algal chloroplast is capable of correctly folding and assembling aglycosylated antibodies that are able to bind their target.…”
Section: Antibodies and Immunotoxinsmentioning
confidence: 99%
“…Pipelines for recombinant biopharmaceuticals now include a growing number of forms and structures, including single‐domain antibodies, fusion proteins, antibody‐drug conjugates, bi‐specific antibodies, and subunit vaccines. This increasing diversity, coupled with increasing global demand for such products at reduced costs, present certain challenges for the host organisms commonly used today for production (Legastelois et al, ; Matthews et al, ). Rapidly advancing technologies for genomic engineering of hosts are promoting renewed consideration of microbial hosts for these tasks (Wagner & Alper, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly advancing technologies for genomic engineering of hosts are promoting renewed consideration of microbial hosts for these tasks (Wagner & Alper, ). Selection of an optimal host for pursuing such purposes, however, can be difficult: many organisms may be suitable hosts, and for each organism, several variants typically exist (Jiang et al, ; Matthews et al, ). A framework for the rational evaluation of potential hosts could further promote the adoption of alternative hosts for commercial protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…Up to this point, all three antibodies were fused to either the S. cerevisiae pre–pro‐α or pre‐α secretion tag, and expressed under the strong methanol inducible promoter pMOX1 , both of which are commonly used for heterologous protein expression in this host. We also observed from the initial work with the anti‐CD20 antibody, the titers of the degraded fragments (as measured by Octet) were always higher in strains where a mannosyltransferase OCH1 was deleted (Table S2), suggesting OCH1 deletion is beneficial for antibody secretion by reducing the degree of hyper‐glycosylation—a known challenge for expression of recombinant proteins in yeast (Matthews et al, ; Tang et al, ). Combining all these parameters, a new set of Herceptin expression constructs were designed with (a) constitutive promoter pTDH3 , (b) new secretion tag from S. cerevisiae invertase Suc2, and (c) targeting the deletion of OCH1 .…”
Section: Antibody Production In Alternative Hostsmentioning
confidence: 67%